Impact of an Educational Program on Nurses Knowledge Regarding the Care of Newborns with Respiratory Distress Syndrome in Neonatal Intensive Care Units (Medical Forum Monthly, 2026)
Objective: To assess the impact of an organized educational intervention on the knowledge of nurses working in the neonatal Intensive care unit on newborns with respiratory distress syndrome.Study Design: A quasi-experimental studyPlace and Duration of Study: This study was conducted at the intensive care units of Babylon Maternity and Children Teaching Hospital and Al-Noor Hospital in Al-Hilla, Babylon Province, Iraq between 1st April 2025 and30th August 2025.Methods: The study was conducted at the 50 neonatal involving 50 nurses working in Babylon Maternity and Children Teaching Hospital neonatal intensive care unit (study group n=25) and Al-Noor Hospital neonatal intensive care unit (control group n=25 The knowledge of the nurses was measured by the use of a validated questionnaire with 5 domains related to the respiratory distress syndrome at pre- and post-test.Findings: The percent of high knowledge level of the study population was 80 percent as opposed to the 24 percent of the control group (p=0.001). The effect of the study group (1.50±0.09 to 1.72±0.07) was significant, whereas in the control group, the effect was minimal (1.54±0.12 to 1.59±0.12). The only demographic variable that was significantly (p<0.05) related to knowledge was educational level.Conclusion: The educational intervention was effective in enhancing the understanding of respiratory distress syndrome among nurses in neonatal intensive care units. The most important factor of understanding was the educational level, which once again demonstrates the need to implement standardized and evidence-based education to enhance neonatal outcomes.